Essays on group decision making under risk - Nieboer, Jeroen (2013)
Economic theory traditionally explains choice under risk through the preferences of the individual, yet many important economic decisions are made by groups. To increase our understanding of the implications of group decisions and enrich our theories accordingly, we need empirical and experimental evidence on groups. Although economists have conducted controlled laboratory experiments on individual choice for many decades, only recently have researchers begun to use the experimental method to study group decisions under risk. This thesis contributes to the study of group decision making under risk by providing a cross-disciplinary review of the growing literature on this topic, followed by three experiments on risk-taking by groups. The first experiment investigates the role of communication and peer effects, the second experiment investigates group composition, and the final experiment focuses on information sharing in groups.